Interações de agentes naturais no controle populacional de Spodoptera frugiperda Smith (1797) (Lepidoptera:Nocturidae) em milho (Zea mays) - Mantrangolo, Walter José Rodrigues (Universidade Federal de São Carlos, 2002)
It was evaluated the possible interactions among the following agents of natural control of Spodoptera frugiperda (Lepidoptera: Noctuidae): Campoletis flavicincta (Hymenoptera: Ichneumonidae), the Nuclear Polyhedrosis Virus (NPV - Sf) and different maize genotypes with different levels of genetic resistance [Resistant exotic parental Zapalote Chico (ZC) (Zea mays), the adapted parental BR 105, and four semi-exotic populations, with different percentages of gene introgression: 50% of ZC + 50% of BR 105 (or simply F1), 25% of ZC + 75% of BR 105 (backcross 1 or simply BC1), 12,5% of ZC + 87,5% of BR 105 (or BC2) and 6,25% of ZC + 93,75% of BR 105 (or BC3)]. The incubation period of the eggs of C. flavicincta was approximately 48 hours. Most of the caterpillars of S. frugiperda contained more than one eggs of the parasitoid. However, 24h after eggs eclosion, it was observed the presence of only one developed larvae in the same caterpillar. Probably there is a competition among newly hatched larvae and through physical attack only one survives. Females of the parasitoid laid more eggs in healthy caterpillar than in infected one, when they did not have choice option. When in contact with healthy caterpillars and infected by NPV - Sf at the same time, there was not difference in the number of deposited eggs, probably because the female could not discriminate between of healthy or NPV infected host. In olfactometer test, healthy S. frugiperda larva and corn leaf attracted 50% of the C. flavicincta females. In the treatment with infected caterpillars and your leaf, they were attracted 32,1% of the females. Where just had leaves, that value was of 14,3% and the witness, without any scent source, it attracted only 3,5% of the females. To discriminate healthy hosts of having infected can minimize the negative impact of NPV - Sf on the parasitoids. Increase of the size of the caterpillar implicates in a reduction in the efficiency of the virus. The united use of virus and parasitoid in laboratory increased the mortality of caterpillars of S. frugiperda in laboratory, when compared with the treatment where was just used the virus. As larger the interval of time between parasitism and infection, larger the survival of C. flavicincta. The previous infection with NPV - Sf reduced the emergency of the parasitóide, mainly in caterpillars infected in the 2nd and 3rd days of life. Not only originated females of caterpillars infected by the virus they were capable to transmit the pathogen for healthy caterpillars, but also those females initially exempt of the virus, but that were coupled with males originating from of infected caterpillars. In laboratory, the genetic materials didn't indicate significant differences in the biological parameters (efficiency of parasitism, weight of healthy caterpillars and sponged, weigh of the pupas, duration of the phase pupal and sexual reason of the host and of the parasitoid). In the field smallest number was collected of caterpillars of size 3 and any caterpillar of size 4 in ZC, besides smallest number of caterpillars of S. frugiperda, of pupae of the parasitoid and where the damage level was smaller, indicating that there was effect of that material.
Keywords: Controle natural; Milho; Vírus de Poliedrose Nuclear (VPN); Campoletis flavicincta; Zapalote Chico; Doruluteipes; Biodiversidade; CIENCIAS BIOLOGICAS::ZOOLOGIA::ZOOLOGIA APLICADA::CONTROLE POPULACIONAL DE ANIMAIS